Quantitative Analysis of China's Contracted Family Doctor Service Policies Based on a Three-dimensional Analysis Framework - SUN Jiaying, LUO Jinping, ZHANG Qianwen, WANG Kang, YIN Wenqiang, CHEN Zhongming, MA Dongping (Zhongguo quanke yixue, 2024)
Background After being completely promoted for less than seven years, China's contracted family doctor service work still faces a number of development problems. The primary obstacle impeding the work of contracted family doctor service is an inadequate guarantee mechanism. There is an urgent need for scientific and reasonable policies on contracted family doctor service to guarantee the effective development of the work. Objective To quantitatively analyze the textual content of China's contracted family doctor service policies, to explore the focus and shortcomings of the existing policies, and to provide the basis and reference for the development and optimization of the subsequent contracted family doctor service policies. Methods Policy texts were collected by visiting the official websites of the China government and the National Health Commission of the People's Republic of China on 2023-01-10, and 15 policy texts on contracted family doctor service from 2015—2022 were selected to construct a three-dimensional analytical framework of policy tools-stakeholders-policy strength, to categorize, code, and analyze the policy documents. Results Supply-based, demand-based, and environment-based tools accounted for 30.5% (69/226), 19.0% (43/226), and 50.5% (114/226) of the policy tool dimension. Family doctors, contractors, non-contractors, primary medical and health care institutions, hospitals (secondary and above), and the government accounted for 29.2% (123/422), 14.7% (62/422), 9.2% (39/422), 21.3% (90/422), 13.3% (56/422), and 12.3% (52/422) of the stakeholder dimension. The average strength of China's contracted family doctor service policies was 2.2 points. In the cross-dimension of policy tools-stakeholders, the distribution of stakeholders in supply-based and environment-based tools was relatively poor. There were some sub-tools that were absent from the policy tools. In the cross-dimension of policy tools-policy strength, environment-oriented policy instruments were used more often as policy strength increased. In the cross-dimension of stakeholders-policy strength, there were large differences of the policy strength matching scores among various stakeholders. Family doctors had the highest score (311 points) with non-contractors the lowest score (90 points) . Conclusion From the perspective of policy tools, policy tools should be allocated rationally, with the weight of use continuously adjusted, the internal structure optimized, and the rationality of the distribution of policy tools among stakeholders improved. From the stakeholder's perspective, all stakeholders should be taken into account, their respective positions need to be clarified, and the demand of the non-contractors should be emphasized. From the perspective of policy strength, the policy supervision and management capacity ought to be strengthened to continuously improve the implementation of the policy of contracted family doctor service.